MARKETING OF ORGANIC PRODUCTS: A CASE STUDY OF SAMPRAN MODEL: Received: 6th November 2023 Revised: 19th December 2023, 22nd December 2023 Accepted: 16th November 2023 - P. Katepan,; T. Mekhora,; B. Chanthumma, (PEOPLE: International Journal of Social Sciences, 2024)
Green products commonly offer potential benefits to the environment and human health, which consumer preferences in sustainability at the present are continuously increasing. This study investigated the organic or green product distribution channels and marketing strategies of organic vegetable farmers. Survey research with a simple random sampling technique was conducted using 120 Sampran Model Project farmers in Nakhon Pathom province, Thailand. The data were processed and analyzed using a statistical package for the social sciences. The results revealed: 1) 3.50% of the farmers sold organic products via each channel at a high level; and 2) 43.30% of the farmers had no promotion marketing strategy for selling organic products, while 27.50% used a price reduction strategy, and 9.00% used a price reduction strategy with a bonus product/gift, 7.00% applied a price reduction strategy when customers purchased in large quantities, and 7.00% applied a price reduction strategy when customers purchased a specified amount with free shipping, 3.00% used a promotion strategy, such as a sale, exchange, distribution, and giveaway; and 4) the rest of the strategies consisted of reward points collection (0.80%), 10% discount when customers purchased in bulk (0.80%), if customers purchased a specified amount they could visit the farm (0.80%), and a free trial (0.80%).